Design and Establishment of a Small Hydroelectric Plant on the Barrage of Fallujah - Nife, M. (Anbar Journal of Engineering Sciences, 2012)
The world is moving now to the energy of water to generate electric power and too much on several considerations, most important is that this energy is a clean and renewable energies as well as reasonably available. So we are going to create a small hydro power stations with limited power can be linked via the national grid or the completion of feeding limited areas to ease the load on the national network in addition to low cost of establishment and the costs of power processed. And now that we need t this specification at this stage and the availability of waterways and weirs in the governorate of AL-anbar has been building this research. We have in this search by selecting the barrage of Fallujah for the establishment of a hydroelectric plant it was a survey of geographical and engineering on the site of this barrage was recorded the water levels over the full year and found that the height of the water in which at least 3.5 meters, so the choice of equipment needed to build a hydroelectric plant with capacity of (140) KW aided with catalogues of well known international companies and accredited globally.